SURVEI KEPUASAN SEKOLAH MITRA PROGRAM PENGALAMAN LAPANGAN (PPL) TERHADAP KEMAMPUAN MAHASISWA DALAM PEMBELAJARAN - Rina Rosdiana; Tri Mahajani; Indri Yani; Rukmini Handayani (Pedagonal : Jurnal Ilmiah Pendidikan, 2018)
ABSTRACTThe aim of this research is to explain the degree of satisfaction from school partner of internship program on students ability to arrange lesson plan and conduct it also the satisfaction from the school on internship program. This research is a descriptive study with survey method which conducted at schools partner for the internship odd semester 2015/2016 Faculty of Teachers Training and Educational Sciences, Pakuan Universities. There are 42 school partners for the intern program, 32 elementary schools, 5 junior high, 5 senior high, both in private and public school in Bogor. The survey result about school partnership satisfaction on students ability in conducting teaching learning process, especially in arranging lesson plan can be seen as satisfied (70%), very satisfied (20%), and fairly satisfied (10%). The satisfaction of intern partner on students in conducting teaching learning process are 85% says satisfied, 10% says very satisfied, and 5% says fairly satisfied. Satisfaction level on the intern management as seen by the teacher are 60% satisfied, 35% very satisfied, and 5% fairly satisfied, and there are no respondents claiming to have not satisfied.Keywords: intership, satisfaction